1993
DOI: 10.1111/j.1600-0536.1993.tb03483.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical nonsteroidal antiinflammatory drugs: allergic and photoallergic contact dermatitis and phototoxicity

Abstract: In spite of not knowing the numbers of patients treated and incomplete reporting, we review the adverse effects of topical nonsteroidal antiinflammatory drugs, namely, allergic contact dermatitis, photoallergic and phototoxic dermatitis, and attempt to provide a clinical perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 49 publications
(28 reference statements)
2
54
0
4
Order By: Relevance
“…Literatürde etofenamata bağlı tanımlanmış irritan kontakt dermatit bulunmazken allerjik ve fotoallerjik kontakt dermatit birçok kez bildirilmiştir (1,(5)(6)(7)(8). Hatta bir çalışmada etofenamat aril propiyonik asit derivelerinden (deksketoprofen, ketoprofen) sonra ikinci en sık kontakt dermatit ve fotoallerjik kontakt dermatit yapan NSAİİ olarak gösterilmiştir (8).…”
Section: Sayın Editör;unclassified
“…Literatürde etofenamata bağlı tanımlanmış irritan kontakt dermatit bulunmazken allerjik ve fotoallerjik kontakt dermatit birçok kez bildirilmiştir (1,(5)(6)(7)(8). Hatta bir çalışmada etofenamat aril propiyonik asit derivelerinden (deksketoprofen, ketoprofen) sonra ikinci en sık kontakt dermatit ve fotoallerjik kontakt dermatit yapan NSAİİ olarak gösterilmiştir (8).…”
Section: Sayın Editör;unclassified
“…In particular, the nonsteroidal antiinflammatory 2-arylpropionic acids deserve special attention because they induce such disorders more frequently than other types of drugs [4][5][6]. Tiaprofenic acid (TPA) is a member of this family, that has been found to be one of the most potent photosensitizers in a multicenter photopatch test trial [5,6].…”
Section: A Model Group Of Drugs For Photosensitization Studiesmentioning
confidence: 99%
“…Numerous reports document phototoxic and photoallergic contact dermatitis from systemic piroxicam, tiaprofenic acid, ketoprofen, carprofen and benoxaprofen [17]. NSAIDs that are structurally related to propionic acid have been shown to possess phototoxic potential, whereas certain other types of NSAIDs, such as piroxicam, were not experimentally phototoxic but demonstrated clinical photosensitivity [17]. However, Sugiura et al [18] carried out photopatch testing with ketoprofen on 335 patients and found there was only 1 case with a positive reaction.…”
mentioning
confidence: 99%
“…The mechanism of photosensitivity of topical NSAIDs is still not clearly defined [16,17]. Numerous reports document phototoxic and photoallergic contact dermatitis from systemic piroxicam, tiaprofenic acid, ketoprofen, carprofen and benoxaprofen [17]. NSAIDs that are structurally related to propionic acid have been shown to possess phototoxic potential, whereas certain other types of NSAIDs, such as piroxicam, were not experimentally phototoxic but demonstrated clinical photosensitivity [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation